2005
DOI: 10.1038/labinvest.3700213
|View full text |Cite
|
Sign up to set email alerts
|

Small proline-rich proteins 2 are noncoordinately upregulated by IL-6/STAT3 signaling after bile duct ligation

Abstract: Small proline-rich proteins 2 (SPRR2) are coordinately expressed with other epidermal differential complex (EDC) genes in the skin. They function as crosslinking proteins that form bridges between other proteins that comprise the cornified cell envelope, which is the major barrier against the environment. IL-6 is invariably produced at sites of biliary tract injury and IL-6-deficient (IL-6 À/À ) mice show impaired barrier function after bile duct ligation (BDL). Screening microarray analysis identified noncoor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 42 publications
3
31
0
1
Order By: Relevance
“…Similarly, Sprr genes are strongly upregulated in intestinal epithelium both in response to bacterial colonization and with induction of allergic gastrointestinal inflammation (62,63). Duct ligation results in SPRR gene induction in biliary epithelial cells related to recovery of barrier function (64). These results suggest that there is a common stress response within epidermal, intestinal, bronchial, and biliary epithelium in response to infection.…”
Section: Impaired Barrier and Skin Inflammatory Disorders: Atopic Dermentioning
confidence: 65%
“…Similarly, Sprr genes are strongly upregulated in intestinal epithelium both in response to bacterial colonization and with induction of allergic gastrointestinal inflammation (62,63). Duct ligation results in SPRR gene induction in biliary epithelial cells related to recovery of barrier function (64). These results suggest that there is a common stress response within epidermal, intestinal, bronchial, and biliary epithelium in response to infection.…”
Section: Impaired Barrier and Skin Inflammatory Disorders: Atopic Dermentioning
confidence: 65%
“…Evidence has shown that SPRR2 proteins participate in the response to various stresses in many tissues without a stratified epithelium. In the biliary tract, the expression of SPRR2 members is highly induced under stress injury [29]. Similarly, SPRR1A and SPRR2A are strongly induced in cardiomyocytes responding to biomechanical/ischemic stress, and these proteins could protect cardiomyocytes against ischemic injury [30].…”
Section: Discussionmentioning
confidence: 99%
“…IL6 is not a direct mitogen for hepatocytes and does not enhance the mitogenic effect of other growth factors. It is, however, a direct mitogen for biliary cells (Liu et al, 1998) and it has important effects on integrity of the intrahepatic biliary tree by regulating production of small proline-rich proteins by cholangiocytes (Nozaki et al, 2005;Demetris et al, 2006). IL6 does increase in plasma following PHx.…”
Section: Interleukin 6 (Il6)mentioning
confidence: 99%